Trends in High-grade Cervical Lesions and Cervical Cancer Screening in 5 States, 2008–2015. (23rd August 2018) - Gargano, Julia Warner; Park, Ina U; Griffin, Marie R; Niccolai, Linda M; Powell, Melissa; Bennett, Nancy M; Johnson Jones, Michelle L; Whitney, Erin; Pemmaraju, Manideepthi; Brackney, Monica; Abdullah, Nasreen; Scahill, Mary; et al.
Abstract : We describe trends in high-grade cervical lesions (CIN2+), identified through population-based surveillance in 2008–2015. In addition to changed screening recommendations, observed CIN2+ declines among screened women aged 18–24 years indicate a population-level impact of human papillomavirus vaccination. Abstract: Background: We describe changes in rates of cervical intraepithelial neoplasia grades 2, 3 and adenocarcinoma in situ (CIN2+) during a period of human papillomavirus (HPV) vaccine uptake and changing cervical cancer screening recommendations. Methods: We conducted population-based laboratory surveillance for CIN2+ in catchment areas in 5 states, 2008–2015. We calculated age-specific CIN2+ rates per 100000 women by age groups. We estimated incidence rate ratios (IRR) of CIN2+ for 2-year periods among all women and among screened women to evaluate changes over time. Results: A total of 16572 CIN2+ cases were reported. Among women aged 18–20 and 21–24 years, CIN2+ rates declined in all sites, whereas in women aged 25–29, 30–34, and 35–39 years, trends differed across sites. The percent of women screened annually declined in all sites and age groups. Compared to 2008–2009, rates among screened women were significantly lower for all 3 periods in women aged 18–20 years (2010–2011: IRR 0.82, 95% confidence interval [CI] 0.67–0.99; 2012–2013: IRR 0.63, 95% CI 0.47–0.85; 2014–2015: IRR 0.44, 95% CI 0.28–0.68) and lower for the latter 2 time periods in women aged 21–24 years (2012–2013: IRR 0.86, 95% CI 0.79–0.94; 2014–2015: IRR 0.61, 95% CI 0.55–0.67). Conclusions: From 2008–2015, both CIN2+ rates and cervical cancer screening declined in women aged 18–24 years. The significant decreases in CIN2+ rates among screened women aged 18–24 years are consistent with a population-level impact of HPV vaccination.